Ethnographies in the continental Caribbean of Central America: critical analysis of afrodiaspora - Vásquez Pino, Daniela (2025)
This article review analyses three books that explore the experiences of communities of African descent in the Central American mainland Caribbean. In their 2019 study, anthropologist Edmund T. Gordon presents a 35-year analysis of the African diaspora in Bluefields, Nicaragua. Their research employs an intersectionality approach, focusing on the analysis of political commonsense and racial economy in Creole. In their 2021 study, anthropologists Serena Cosgrove et al. examine the resistance and resilience of the Garifuna community in Nicaragua, its links to Honduras and different migrations. They challenge concepts of culture and resistance by focusing on Garifuna communities in the Bronx, USA. Cultural anthropologist Carla Guerrón Montero (2023) examines the transformation of the Afro-Antillean population in Bocas del Toro, Panama, as a result of tourism. Based on ethnographic and historical research, the studies reveal how these communities cope and adapt their identities in the context of external factors such as tourism, migration and racial economies. They provide an in-depth understanding of cultural resistance and power dynamics.